Sr2GdF7:Tm3+/Yb3+ glass ceramic: A highly sensitive optical thermometer based on FIR technique - Chen, WeiPing; Cao, JiangKun; Hu, FangFang; Wei, RongFei; Chen, LiPing; Guo, Hai (Journal of alloys and compounds, 2018)
In this work, we present a highly sensitive optical thermometer, Tm3+/Yb3+ co-doped Sr2GdF7 transparent oxyfluoride glass ceramic (GC). Sr2GdF7:Tm3+/Yb3+ GC was synthesized by traditional melt-quenching method with further crystallization process. Its structural and optical properties were systematically investigated by a series of characterization methods. The enrichment of Tm3+ into Sr2GdF7 lattice is confirmed by enhanced emission intensities, obvious Stark splitting and prolonged lifetimes of Tm3+ after crystallization. Based on fluorescence intensity ratio (FIR) of 3F3 → 3H6 and 1G4 → 3F4 transitions of Tm3+, the temperature thermometric properties of Sr2GdF7:Tm3+ GC were explored. Interestingly, maximum relative sensitivity SR-max reaches 1.97% K−1 at 353 K and the absolute sensitivity SA keeps increasing with temperature up to 3.90% K−1 at 563 K. Our investigation demonstrates that Sr2GdF7:Tm3+/Yb3+ GC may act as promising candidate for optical temperature sensor. •Transparent Sr2GdF7:Tm3+/Yb3+ glass ceramic (GC) was successfully fabricated.•Up-conversion of Sr2GdF7:Tm3+/Yb3+ GC is high enhanced compared to that of PG.•Sr2GdF7:Tm3+/Yb3+ GC present large energy gap (2207 cm−1) and high relative sensitivity (SR-max reaches 1.97%K−1 at 353 K).•Sr2GdF7:Tm3+/Yb3+ GC may find application in FIR-based temperature sensors.